PEMBELAJARAN MODEL KOOPERATIF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PADA KEMAMPUAN PEMECAHAN MASALAH MATERI PECAHAN SISWA KELAS IV SD - Abdul Rahman; Sylvia Rabbani (COLLASE (Creative of Learning Students Elementary Education), 2021)
This  study  aims  to  determine efforts  to  improve  mathematics  learning achievement  using  cooperative  learning  model  Student Team Achievement Division  four  grade  students  of elementary  Plus  Al-Aitaam and the  application  of  STAD  cooperative  learning model  to  improve  student’s problem solving skills.  STAD  cooperative  learning  model  is  a learning technique cooperative which invites students to discuss, help each other and  work  together  to  accomplish  tasks  of  teachers.  Cooperative  learning  model STAD  can  also  train  students  in  the  skills  of  working  and  completing  tasks assigned by the teacher. Applied research by researchers is a class action. Subjects were students of class  IV  SD  Plus Al-Aitaam  totaling  30  students. The instrument used  for  this  study  is  a  short  essay  test  prepared  by  the  researchers.  The  data analysis technique used is qualitative  descriptive techniques, to examine the data that is by collecting student test  results, convert raw scores into grades so, finding the average and compared with that of the previous conditions.   The  experiment was conducted in  tri  meeting. Based on the results of research and of  the discussion on this research, it can be deduced that there is the representation of the student mathematical 4rd class especially on math material floating STAD after enactment of the model.